Enzymatic Degradation Properties of Silk Fibroin Film (Journal of Fiber Bioengineering and Informatics, 2018)
The degradation behavior of silk fibroin biomaterials in human body is definitely vital for the growthof tissues. Therefore, an investigation to regulate the degradation behaviors of silk fibroin films bychanging the degree of cross-linking is presented in this paper. The in-vitro experiments in the simulatedhuman body environment showed that the degradation rate of cross-linked silk fibroin films was inverselyproportional to the degree of cross-linking. After degradation, the ratio of crystalline part in the SFfilms increased. This approach would provide a new direction in controlling the degradation time bycross-linking the silk fibroin for specific tissue engineering application.